2017
DOI: 10.12973/ejmste/78194
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Spence Children’s Anxiety Scale (SCAS)

Abstract: The aim of this study is to explain the validity and reliability of the SCAS translated into Turkish language, as well as testing the validity of the 6-factor model among the Turkish Republic of Northern Cyprus (TRNC) population. The sampling group consists of 461 students studying in the 4th and 5th grade of 11 primary schools selected randomly among 112 primary schools in Northern Cyprus under the Ministry of National Education. 48.80% of these students were female (N = 225) and 51.20% were male (N = 236). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
7
1
Order By: Relevance
“…Hence, the authors compared the SPAS anxiety scores obtained in the present study with the norm values specified for Turkish preschool children. 11 In the present study, although the general anxiety and obsessive-compulsive disorder data was found to be lower than the norm values, the total SPAS anxiety scores were found to be higher than in the norm study. This difference was due to the higher levels of separation anxiety and physical injury anxiety observed in the present study.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…Hence, the authors compared the SPAS anxiety scores obtained in the present study with the norm values specified for Turkish preschool children. 11 In the present study, although the general anxiety and obsessive-compulsive disorder data was found to be lower than the norm values, the total SPAS anxiety scores were found to be higher than in the norm study. This difference was due to the higher levels of separation anxiety and physical injury anxiety observed in the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…The one-sample t test analysis was carried out to analyze differences between the anxiety levels obtained in the present study and the mean scores reported in the norm study. 11 The post hoc Šídák pairwise comparison test was performed to determine whether the values obtained for the anxiety subdimensions in the present study were statistically significantly different or not, and to rank the values of the anxiety subdimensions. Categorical data was recorded as number (n) and percentage (%), and quantitative data as mean (M) and standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCARED questionnaire was developed "based on anxiety symptoms in clinical populations" for children 8 to 18 years [27], while SCAS measures anxiety symptoms in children aged 8 to 12 years. Additionally, PAS was developed for children aged 3 to 6 years to assist in clinical assessments and determine whether children are showing higher levels of anxiety [28][29][30]. Although these tools check anxiety levels in children, there is no tool to screen for the possible presence of anxiety in young children within the unique cultural context of South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…At the best knowledge of the authors, there have been many researches on the validity and reliability of the instruments to measure anxiety, but they have not especially dealt with digital instruments, the Internet, and the like. For instance, decades ago, the studies were focused on the validity and reliability of State-Trait Anxiety Inventory (Metzger, 1976), measurement of the validity in the Foreign Language Anxiety Scale instrument (Aydin et al, 2016), measurement of the validity in the Spence Children's Anxiety Scale (SCAS) (Direktör & Serin, 2017), validity and reliability testing of the Depression, Anxiety and Stress Scale (DASS) (Basha & Kaya, 2016), and the validity and reliability screening in the depression and anxiety disorders (Marrie et al, 2018). Therefore, it is greatly necessary to have a basically adequate instrument (Bajpai & Bajpai, 2014) since it will give impacts on the generalization or scientific inferences (Hall et al, 2014;Messick, 1994) and it also may be used as the clinical assessment or as the empirical development of science.…”
Section: Introduction mentioning
confidence: 99%